Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Speleothem multi-proxy inferred hydroclimate variability during the 2.8 ka event and its influence on human activities in southeastern China - Xiaomei Zhang; Haiwei Zhang; Ashish Sinha; Miaomiao Wang; Jian Wang; Yueer Li; Liangkang Pan; Rui Zhang; Youfeng Ning; Xuexue Jia; Baoyun Zong; Hai Cheng (Global and Planetary Change, 2026)

Supramolecular nanomedicine reprogramming calcium ions metabolism for cancer cell PANoptosis and immunotherapy - Yongjuan Li; Danyang Shen; Xianlong Zong; Furu Gong; Xinran Zhu; Jiajia Wu; Hongfei Xue; Haochen Yao; Rui Li (Science Bulletin, 2026)

Wide-precision planting with optimal high sowing rate improves winter wheat yield by optimizing canopy structure and radiation use - Yunchao Liu; Rui Zong; Yanli Fan; Miaomiao Qiao; Haojie Hu; Xinghui Wang; Quanqi Li (Field Crops Research, 2026)

Optimizing water use and biodiversity outcomes in soybean–maize strip intercropping systems - Zhendong Liu; Xiudi Shangguan; Huaiyu Mu; Jiahao Zhou; Linyao Li; Shishuo Li; Rui Zong; Xianghao Hou; Yanli Fan; Mingming Zhang; Quanqi Li (Agricultural Systems, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Monovalent cation–anion pairing governs scaling and particulate fouling in saline water distribution systems: Evidence from K⁺-salt dosing - Changjian Ma; Weiyi Zhang; Enkai Cao; Shishuo Li; Rui Zong; Yang Xiao; Xinhao Gao (Journal of Environmental Chemical Engineering, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Maize-soybean intercropping improves grain yield via modifying water uptake strategies and dry matter accumulation translocation mechanisms - Zhendong Liu; Xiudi Shangguan; Haojie Hu; Xinghui Wang; Miaomiao Qiao; Yunchao Liu; Zhiheng Liang; Rui Zong; Quanqi Li (Field Crops Research, 2026)

Automatic Image Co-registration of Carotid Angiography and Intravascular Optical Coherence Tomography Based on Machine Learning Method: A Pilot Feasibility Study - Hui Xu; Jia-Nan Li; Yan Xu; Jun-Ren Ma; Kang Zong; Rui Zhu; Yi-Hui Cao; Peng-Fei Yang; Rui Zhao; Jian-Min Liu (Annals of Biomedical Engineering, 2026)

A block theory-based method for identifying the boundaries and movement modes of potential unstable bodies in rock slopes - Qinkuan Hou; Shuhong Wang; Rui Yong; Zong Li; Wenshuai Han; Wenpan Sun (Rock Mechanics and Rock Engineering, 2025)

Sub-soil biodegradable film mulching: A sustainable solution for enhancing winter wheat yield and shaping soil microbial communities in saline-alkali soils - Changyuan Wang; Junwei Dong; Boxiang Ji; Yahui Lv; Yixuan Song; Quanqi Li; Chitao Sun; Rui Zong; Mingming Zhang (Journal of Hazardous Materials, 2025)

Identification and functional characterization of ssDNA in plants - Zhaoguo Li; Mahmoud Tavakoli; Rui Jiang; Lixin Zong; Wenli Zhang (Trends in Plant Science, 2025)

A case study on facing climate change: optimizing planting density and date of summer maize for stable grain yield in the North China Plain - Zhendong Liu; Shiyu Wei; Xiudi Shangguan; Xin Wang; Meng Yuan; Rui Zong; Quanqi Li (Regional Environmental Change, 2025)

Novel approaches for alleviating shallow soil compaction using microbial fertilizers and their beneficial impacts on plant growth and soil physicochemical properties - Xiang Yao; Hailin Guo; Dandan Li; Junqin Zong; Rui Zhang; Jingbo Chen; Dongli Hao; Xinyong Zhao; Jianxiu Liu; Haoran Wang; Chunjie Li (Soil and Tillage Research, 2025)

Schisandrin A alleviates non-alcoholic fatty liver disease by improving liver metabolic disorders and suppressing the GSK3β signaling pathway - Li Zong; Rui Xu; Yunxia Sun; Junjie Qiu; Huihui Tao; Chengyu Shentu; Hongxia Niu; Tengfei Xu; Yuan Zhou (Food Bioscience, 2024)

New insights into the mechanisms and therapeutic strategies of chondrocyte autophagy in osteoarthritis - Lujia Tang; Jiatong Ding; Kangping Yang; Zhen Zong; Rui Wu; Hui Li (Journal of Molecular Medicine, 2024)

Activation technology of steel slag for concrete exposed to plateau climate: a state-of-the-art review - Wei Deng; Rui Xiong; Xinming Zhai; Kai Huang; Liding Li; Youjie Zong; Haoyu Wang; Jianliang Zhai; Hao Lai; Nan Mao; Changchun Shi; Fuyang Lu (Environmental Science and Pollution Research, 2024)

Kinetically accelerated lithium storage in (LiFeCoNiMnCr)2O3 enabled by hollow multishelled structure, oxygen vacancies and high entropy engineering - Fengfeng Dong; Rui Wang; Yao Lu; Haoyu Xu; Quan Zong; Lijing Yan; Xianhe Meng; Tingli Ma; Dongyun Li; Qingyi Lu; Lizong Dai; Qiaoling Kang (Chemical Engineering Journal, 2024)

Long-term mulched drip irrigation enhances the stability of soil aggregates by increasing organic carbon stock and reducing salinity - Mingdong Tan; Wenhao Li; Rui Zong; Xuanzhi Li; Yue Han; Pengcheng Luo; Yam Prasad Dhital; Haixia Lin; Haiqiang Li; Zhenhua Wang (Soil and Tillage Research, 2024)

Synergistic impact of various straw-return methods and irrigation regimes on winter wheat physiological growth and yield - Fuying Liu; Mingliang Gao; Haoze Zhang; Huabin Yuan; Bin Hu; Rui Zong; Mingming Zhang; Yuzhao Ma; Quanqi Li (Field Crops Research, 2024)

In situ profiling reveals spatially metabolic injury in the initiation of polystyrene nanoplastic-derived intestinal epithelial injury in mice - Xianan Zhang; Jing Wang; Yuansheng Liu; Hemin Wang; Bin Li; Qing Li; Yi Wang; Yuru Zong; Jiajia Wang; Qingtao Meng; Shenshen Wu; Rongzhang Hao; et al. (Science of The Total Environment, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Co-application of concentrated biogas slurry and pyroligneous liquor mitigates ammonia emission and sustainably releases ammonium from paddy soil - Zichuan Li; Rui Zhang; Jianfeng Jiang; Yanjun Chai; Haijun Yang; Yutong Zong; Wenbin Tong; Mengting Yuan; Ronghui Li; Lanting Wang; Shengdao Shan; Ming Hung Wong (Science of The Total Environment, 2024)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Responses of soil nutrient and enzyme activities to long-term mulched drip irrigation (MDI) after the conversion of wasteland to cropland - Mingdong Tan; Rui Zong; Haixia Lin; Yam Prasad Dhital; Olusola O. Ayantobo; Pengpeng Chen; Haiqiang Li; Rui Chen; Zhenhua Wang (Applied Soil Ecology, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Effects of practicing long-term mulched drip irrigation on soil quality in Northwest China - Rui Zong; Zhenhua Wang; Wenhao Li; Haiqiang Li; Olusola O. Ayantobo (Science of The Total Environment, 2023)

Assessing the impact of seasonal freezing and thawing on the soil microbial quality in arid northwest China - Rui Zong; Zhenhua Wang; Wenhao Li; Olusola O. Ayantobo; Haiqiang Li; Libing Song (Science of The Total Environment, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

Changes in the gut microbiota of osteoporosis patients based on 16S rRNA gene sequencing: a systematic review and meta-analysis - Rui Huang; Pan Liu; Yiguang Bai; Jieqiong Huang; Rui Pan; Huihua Li; Yeping Su; Quan Zhou; Ruixin Ma; Shaohui Zong; Gaofeng Zeng (Journal of Zhejiang University-SCIENCE B, 2022)

Soil salinity variations and cotton growth under long-term mulched drip irrigation in saline-alkali land of arid oasis - Wenhao Li; Zhenhua Wang; Jinzhu Zhang; Rui Zong (Irrigation Science, 2022)
The sustainable development and utilization of saline-alkali land are closely related to holding fast the minimum cultivated land area of China. The change of soil salt in cotton field under long-term mulched drip irrigation (MDI) is connected with the development of the national cotton industry. From 2015 to 2019, five cotton fields with different applying years of MDI, which were reclaimed in 2004, 2008, 2010, 2012 and 2015 respectively and were saline-alkali wasteland before, were monitored continuously in the Manas River irrigation area of Xinjiang. By means of continuous location monitoring and spatial–temporal variability (For example, the monitoring data of cotton fields under MDI in 2004, 2008, 2010, 2012 and 2015, and in the year of 2015 were counted as 12, 8, 6, 4 and 1 years, respectively), the spatial–temporal variations of soil salt and ions in cotton field with 1-16a MDI technology were presented. The cotton growth characteristics and its main influencing factors were also analyzed in the study. The results showed that saline-alkali cotton field experienced changed from intensive saline soil to moderate saline soil and finally to non-saline soil under long-term MDI. The change of soil salt and the response of cotton growth to soil salt were divided into three typical stages. Firstly, soil desalinated rapidly in 1-4a MDI cotton field, which the annual average desalination rate was 24.93% in 0–100 cm soil layer (root zone). Additionally, the survival rate of cotton rocketed from 1.48% to 42.04%, and yield increased sharply from 72.43 kg ha −1 to 3075.90 kg ha −1 . Soil desalination was lower in 5-11a MDI cotton field, which the annual average desalination rate was 10.92% at the root zone. The annual survival rate and yield of cotton increased by 6.26% and 5.18%, respectively. After 12a MDI, the soil salt in cotton field tended to be generally constant, which the average salt content in root zone was less than 2.49 g kg −1 . The survival rate of cotton was stable above 90.39%, and the yield per unit area exceeded 5401.32 kg ha −1 . Ions, sodium absorption ratio and Cl − and SO 4 2− equivalent ratio (CSER) in cotton soil also decreased with the extension of MDI. Salt composition changed year by year, but the type of intensive saline soil had always been chloride-sulphate solonchak (0.2 < CSER < 1). In practice, with a higher irrigation quota and ideal irrigation water quality, the soil salt environment of saline-alkali soil MDI cotton field had developed in favor of cotton growth in an oasis irrigation area. However, this management practice caused between 124.21–143.61 mm of water resources waste. Therefore, we should further enhanced the consciousness of water-saving and implemented quota management in practice.

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Psychroflexus maritimus sp. nov., isolated from coastal sediment - Yan-Lin Zhong; Rui Zhang; Xiao-Yu Zhang; Li-Xue Yu; Meng-Fan Zhao; Zong-Jun Du (Archives of Microbiology, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

Pedobacter changchengzhani sp. nov., isolated from soil of Antarctica - Rui-Han He; Zhen-Wei Liu; Yong Yu; Hui-Rong Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2019)

Genetic diversity and phylogenetic analysis of Aleutian mink disease virus isolates in north-east China - Xue Leng; Dongxu Liu; Jianming Li; Kun Shi; Fanli Zeng; Ying Zong; Yi Liu; Zhibo Sun; Shanshan Zhang; Yadong Liu; Rui Du (Archives of Virology, 2018)

Photosynthetic response of Bangia fuscopurpurea (Bangiales, Rhodophyta) towards dehydration and hyposalinity - Wen Jun Wang; Zong Gen Shen; Xiu Tao Sun; Fu Li Liu; Zhou Rui Liang; Fei Jiu Wang; Jian Yi Zhu (Biologia, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Enantioconvergent hydrolysis of racemic styrene oxide at high concentration by a pair of novel epoxide hydrolases into (R)-phenyl-1,2-ethanediol - Rui Wang; Die Hu; Xuncheng Zong; Jinping li; Lei Ding; Minchen Wu; Jianfang li (Biotechnology Letters, 2017)

Mineralogy and isotope geochemical characteristics for Xiaozhen copper deposit, Langao County, Shaanxi Province and their constraint on genesis of the deposit - Gang Wang; Zong-qi Wang; Rui Shi; Ying-li Zhang; Kun-ming Wang (Geosciences Journal, 2015)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Involvement of p38MAPK/NF-κB Signaling Pathways in Osteoblasts Differentiation in Response to Mechanical Stretch - Liang Wang; Jian-yu Li; Xi-zheng Zhang; Lu Liu; Zong-ming Wan; Rui-xin Li; Yong Guo (Annals of Biomedical Engineering, 2012)

Oceaniovalibus guishaninsula gen. nov., sp. nov., A Marine Bacterium of the Family Rhodobacteraceae - Keshao Liu; Rui Zong; Qipei Li; Yingnan Fu; Yongle Xu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

Chaiqin Chengqi Decoction decreases IL-6 levels in patients with acute pancreatitis - Ling Wang; Yuan Li; Qin Ma; Yong Liu; Yuan-yi Rui; Ping Xue; Zong-guang Zhou (Journal of Zhejiang University-SCIENCE B, 2011)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)